Self-Fulfilling Risk Panics - Bacchetta, Philippe; Tille, Cédric; Wincoop, Eric van (American Economic Review, 2012)
Recent crises have seen large spikes in asset price risk. We propose an explanation for such panics based on self-fulfilling shifts in beliefs about risk. A negative link between the current level and the future risk of an asset price leads to a circular relationship between the stochastic process of asset price risk and the price itself. Self-fulfilling shifts in perceived risk can be coordinated around a pure sunspot or around a macro fundamental. In a risk panic, a macro fundamental can be a focal point that affects both the magnitude of the panic and subsequent shifts in perceived risk.